Elementary Technical Mathematics

Published by Brooks Cole
ISBN 10: 1285199197
ISBN 13: 978-1-28519-919-1

Chapter 5 - Review - Page 232: 29



Work Step by Step

We simplify using the exponent rule: $\dfrac{x^a}{x^b}=x^{a-b}$ $$ (49x^2) \div (7x^3)=(49\div 7) x^{2-3}=7x^{-1}\\ =\frac{7}{x}.$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.